PERNIKAHAN TANPA PENCATATAN: ISBAT NIKAH SEBUAH SOLUSI? - Nurlaelawati, Euis (Musawa Jurnal Studi Gender dan Islam, 2013)
The Indonesian Islamic family law, through the kompilasi and the Law of Marriage  of 1974, states that a marriage must be concluded in the presence of an official marriage registrar or must be registered. However, the laws differentiate between the religious validity and the state legality of marriage.  They therefore do not consider a marriage as a religiously invalid if the parties concerned fail to register their marriage. In fact, considered illegal by the state, unregistered marriages are not seen as unlawful by religious authorities. It seems clear that the kompilasi is anxious not  to deviate from the classical doctrine of marriage. This paper discusses unregistered  marriage according to Indonesian State Islamic family law and in practical level and its legal impacts. It criticizes the rules on registration of marriage and its solution. Presenting a number of cases of unregistered marriages and some views of relevant authorities, it argues that there have been abuses in the application of the relevant rules on both registration marriage and isbat nikah.